New Knowledge in Information Systems and Technologies Volume 1 - Rocha, Álvaro; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes a selection of articles from The 2019 World Conference on Information Systems and Technologies (WorldCIST'19), held from April 16 to 19, at La Toja, Spain. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges in modern information systems and technologies research, together with their technological development and applications. The book covers a number of topics, including A) Information and Knowledge Management; B) Organizational Models and Information Systems; C) Software and Systems Modeling; D) Software Systems, Architectures, Applications and Tools; E) Multimedia Systems and Applications; F) Computer Networks, Mobility and Pervasive Systems; G) Intelligent and Decision Support Systems; H) Big Data Analytics and Applications; I) Human-Computer Interaction; J) Ethics, Computers & Security; K) Health Informatics; L) Information Technologies in Education; M) Information Technologies in Radiocommunications; and N) Technologies for Biomedical Applications.
My Employer's Prestige, My Prestige -- The Four Major Factors Impacting on the Future of Work -- The Future of the Digital Workforce: Current and Future Challenges for Executive and Administrative Assistants -- Project Management Practices at Portuguese Startups -- Segmentation of Magnetic Anomalies in the Conduct of Archaeological Excavations -- Automatic Document Annotation with Data Mining Algorithms -- Information and Communication Technologies in Creative and Sustainable Tourism -- Digital Strategy for SMEs in the Retail Business to Allow Sales Increase -- Improvement of the Applicability of the General Data Protection Regulation in Health Clinics -- The Use of LinkedIn for ICT Recruitment -- The Role of Technologies: Creating a New Labour Market -- ERP Conceptual Ecology -- Data Quality Mining -- Trusted Data's Marketplace -- An approach to GDPR based on Object Role Modeling -- Patterns of Ambiguity in Textual Requirements Specification -- Absenteeism prediction in Call Center Using Machine Learning Algorithms.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence